OPTIMIZATION OF POWDER COATING PROCESS PARAMETERS IN MILD STEEL (SPCC-SD) TO IMPROVE DRY FILM THICKNESS - Sukarman; Shieddieque, Apang Djafar; Anwar, Choirul; Rahdiana, Nana; Ramadhan, Anwar Ilmar (Journal of Applied Engineering Science, 2021)
This study presents a comprehensive review of the improved optimization for powder coating process variables in mild steel (SPCC-SD). The effective thickness of the dry film thickness (DFT) keeps a significant influence on the critical protection of mild steel against rust. In the powder coating process, the variable thickness is one of the primary and difficult objectives to accurately control the desired consistency. This empirical study properly uses RAL 7040 epoxy-polyester with the required thickness between 70-100 microns. This empirical study aims to reasonably achieve the optimal value of the effective thickness of the powder layer from specific combinations of specified process criteria. Practical experiments were properly conducted out manipulating an orthogonal Taguchi L16 array of independent variables; program, distance, application method, and the number of layers. This optimization method has been successfully upgraded. The average thickness of the powder coating layers reaches 84.85 microns. For a given limit, the application-method of typically preventing the determined cause correctly examined efficiently provides the most significant effect on effective thickness with an S/N ratio of 0.91. In the future, the relevant research may use our corresponding results to improve the powder coating procedure for other significant impacts.